2011
DOI: 10.1590/s0104-11692011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus detection in the mouth of housekeepers

Abstract: This study assessed the prevalence of colonization by Staphylococcus aureus in hospital housekeepers, and their knowledge and beliefs regarding this problem. Three saliva samples were collected and a questionnaire regarding knowledge and beliefs was applied. Of the 92 workers, 63 (68.5%) participated in the study; 20 were not and 43 were colonized; 13 by Detección de Staphylococcus aureus en la boca de trabajadores de la limpieza hospitalariaEste estudio evaluó la prevalencia de la colonización por Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
1
3
0
1
Order By: Relevance
“…As for the characterization of the population surveyed in this study, there is convergence with the results of other surveys of employees who worked in the cleaning area in the hospital, in which there was a predominance of females and older than 30 years old (3,9,11) .…”
Section: Discussionsupporting
confidence: 72%
“…As for the characterization of the population surveyed in this study, there is convergence with the results of other surveys of employees who worked in the cleaning area in the hospital, in which there was a predominance of females and older than 30 years old (3,9,11) .…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, S. aureus has also been frequently detected among the oral flora, and it may play an important role in both health and disease [107]. The prevalence of S. aureus in saliva or at the oral mucosa ranges from 4% [108] to 64% [109] in healthy populations to (41-68%) in the saliva of healthcare providers [110, 111]. In dental plaque of healthy adults, S. aureus was isolated with a frequency of 24 to 36% [112].…”
Section: Staphylococcus Aureus In the Oral Cavitymentioning
confidence: 99%
“…performed a study that concluded that the total occurrence rate of staphylococcus species in saliva was 83.9% . According to Cruz et al ., the mouth is recognized as a source of bacteremia in infective endocarditis . The authors reported that there is an increasing number of reports suggesting that staphylococci from an oral source may cause infection at sites distinct than the mouth.…”
Section: Resultsmentioning
confidence: 99%